Cross-sectional study of pattern of Dyslipidemia and Prevalence of Atherogenic Diabetic Dyslipidemia in newly detected Diabetic patients - Krishnamurthy, Vinay; Kerekoppa, Akhila Rao; B, Prabhakar (Asian Journal of Medical Sciences, 2019)
Background: India has seen an ever increasing number of diabetic patients and in turn rise in cardiovascular diseases. Many studies have shown diabetic patients to have dyslipidemia, with certain common patterns early in the disease. Aims and Objective: The current study was done to identify pattern of dyslipidemia and prevalence of ADD in treatment naïve diabetic patients. Material and Methods: Fasting lipid profile was analysed in treatment naïve diabetic patients at a tertiary care teaching hospital. Various factors influencing the results were analysed statistically. Results: Prevalence of dyslipidemia was 89.2%, whereasatherogenic diabetic dyslipidemia was seen in 34.2% and raised non-HDL cholesterol in 73.3%. Conclusion: Our study showed a high prevalence of dyslipidemia in newly diagnosed diabetics indicating the importance of screening for dyslipidemia in newly diagnosed cases and implementation of timely lipid lowering therapy to prevent CVD. It also highlights the importance of pattern of dyslipidemia called Atherogenic diabetic dyslipidemia and raised Non-HDL cholesterol in diabetic patients.